Effects of half-dose and full-dose GnRH antagonists on IVF-ET outcomes: a retrospective study - Yingge Zhao; Fang Lian; Shan Xiang; Yi Yu; Conghui Pang; Yue Qiu (BMC, 2021)
Abstract Background Gonadotropin-releasing hormone antagonist(GnRH-ant) has been shown to have a negative effect on endometrial receptivity. Therefore, the use of lower doses of GnRH-ant during controlled ovarian stimulation (COS) may improve endometrial receptivity and clinical pregnancy rate. However, the GnRH-ant dose is relatively flexible and there is no fixed requirement for guidance. In this retrospective study, we determined the effects of half-dose and full-dose GnRH-ant on IVF-ET outcomes. Methods Of the 316 cycles in the 314 patients analyzed in this study, 149 received GnRH-ant half-dose (Group1), while 167 received GnRH-ant full-dose (Group2). The groups were further classified based on age and BMI. Age subgroups, were divided as age ≤ 35(subgroup A) and age > 35(subgroup B): 180 cycles in subgroup A (107 cycles in subgroup A1,73 cycles in subgroup A2), 136 cycles in subgroup B (42 cycles in subgroup B1,94 cycles in subgroupB2). The subgroups based on BMI were divided as BMI < 25 (subgroup C)and BMI ≥ 25 (subgroup D):208 cycles in subgroup C (94 cycles in subgroup C1,114 cycles in subgroup C2), 108 cycles in subgroup D (55 cycles in subgroup D1,53 cycles in subgroup D2). Results The number of fertilized oocytes, superior-quality embryos, clinical pregnancy rate, and live birth rate differed significantly between the two groups. However, the number of retrieved oocytes and available embryos were significantly higher in Group 1 than Group 2 (8.17 ± 4.10 vs. 7.07 ± 4.05, 2.96 ± 2.03 vs. 2.52 ± 1.62, respectively,p<0.05). Differences between the age subgroups were not statistically significant. However, in the subgroups based on BMI, the fertilized oocytes, available embryos, the number of superior-quality embryos, and the live birth rate differed significantly between the four subgroups. The number of retrieved oocytes was higher in subgroup C1 than in subgroup C2 (8.24 ± 4.04 vs. 6.83 ± 3.92,p < 0.05), In addition, the clinical pregnancy rate was slightly higher in subgroup D1 than in subgroup D2(45.45 vs. 24.53%, P < 0.05). Conclusions The results showed that half-dose GnRH-ant was as effective as full-dose GnRH-ant for most patients. Moreover, half-dose GnRH-ant may be more suitable in patients with BMI greater than or equal to 25. The findings of this study need to be validated in a large sample RCT. Trial registration Retrospectively registered.